Echocardiographic Right Heart Study in Patients with Chronic Obstructive Pulmonary Disease (Medicine Today, 2021)
Introduction: Chronic obstructive pulmonary disease (COPD) has considerable effects on cardiac functions, including those of the right ventricle, left ventricle, and pulmonary blood vessels. Most of the increased mortality associated with COPD is due to cardiac involvement. Echocardiography provides a rapid, noninvasive, portable, and accurate method to evaluate the cardiac changes. Aims: We aimed to prospectively study the patients with diagnosed COPD with echocardiogram for evaluating the right heart.Materials & Methods: Our study was an observational, cross sectional study was done on 50 patients with COPD who were admitted at Department of Cardiology, CMCH and underwent echocardiographic evaluation from November 2017 –October 2018. All echocardiogaphic parameters focused on right heart and its function were assessed.Results: Out of total 50 COPD patients studied, majority of them were male (46 patients ,92%). The mean age group of the studied patients was 58.4 ±7.7 years. Pulmonary hypertension defined as sPAP>30 mmHg was evident in all of the patients; with 30 patients (60%), 14 (28 %) and 6(12 %) patients having severe, moderate and mild pulmonary hypertension respectively. RV dysfunction was evident with reduced average TAPSE values (1.59± 0.38 cm) and elevated RIMP values (0.58±0.16).Conclusion: Majority of COPD patients had evidence of pulmonary hypertension. Echocardiogram can be a helpful tool to assess early changes on the right heart size and function in patients with COPD and also monitor these patients for rapid progression of the illness.Medicine Today 2021 Vol.33(2): 123-128